The Effectiveness of a Suggested Model for Learning through Projects Based on Shared Learning Using Social Communication Networks in Developing Critical Thinking Skills and Self-Efficiency in PNU Students - Wadha H. Al-Otaibi (Sultan Qaboos University, 2016)
The study aimed at identifying the effectivness of a suggested model for learning through projects based on shared learning in developing critical thinking skills and self-efficiency in Princess Nourah bint Abdularhman University (PNU). The study included a sample of 76 students from the specialization of primary level teachers in PNU randomly chosen, in which 39 students represented the experimental group. This group was taught the course of learning through projects using a suggested model. The other 37 students formed the control group and were taught the course in the conventional teaching manner. The critical thinking test and the self-efficiency scale were both administered before and after the experiment. The study revealed a significant difference (p < 0.05) in the means between the experimental and control groups in the critical thinking skills test and the self-efficiency sclae in favor of the experimental group.